THE INFLUENCE OF LOCATION AND BRAND IMAGE ON STUDENTS' INTEREST IN TRANSACTING AT BANK RAKYAT INDONESIA SUNGAI PENUH BRANCH OFFICE - Nursitha, Nita; Busni, Darti; Halim, Halim (Asian Journal of Islamic Economic Studies, 2024)
This study intends to investigate the extent of the influence of location and brand image on students' interest in transacting at BRI Kanca Sungai Penuh. The research found that location positively and significantly influenced students' interest in transacting. This contrasts with the brand image, which has no effect on students' transaction interest. However, location and brand image have a positive and significant impact on student interest in transacting, with location being the most influential variable affecting student interest in transacting at BRI Kanca Sungai Penuh. After considering the study's findings, it's clear that the brand image has a relatively low impact on students' willingness to transact. Before using a company's products, students should acknowledge the company's brand image, especially consumer and service firms. This is attributable to the fact that a company's image reflects the quality of its products.